RACISM, GENDER, AND MILITARY REPRESENTATION IN THE SIX TRIPLE EIGHT (2024): A CRITICAL RACE AND BARTHESIAN SEMIOTIC ANALYSIS - Rahmatika Wida Hapsari; Yusrina Dinar Prihatika (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
his study examines the representation of racism in the film The Six Triple Eight within the broader context of cultural, media, and representation studies, where racism is understood as a socially constructed and historically embedded phenomenon. Studies that have already been conducted on racism in movies typically use semiotic analysis or Critical Race Theory (CRT) independently, which leads to disjointed methods that are unable to explain how audiovisual signs function as mechanisms for creating and reproducing racial ideology. This study addresses this research gap by integrating CRT and Roland Barthes’ semiotics into a unified analytical framework. This study aims to identify the types of racism depicted in The Six Triple Eight and examine the ways in which these depictions carry ideological meanings. Purposive sampling is used in this study’s descriptive qualitative methodology to select settings that both overtly and covertly represent racism. Repeatedly watching the movie, taking methodical notes, and documenting screenshots as visual evidence are some methods for gathering data. Three steps comprise the analytical process: first, identifying pertinent visual, verbal, and symbolic signs; second, using Barthesian semiotics to interpret their meanings at the levels of denotation, connotation, and myth; and third, contextualizing these meanings using CRT to reveal systemic racial structures and underlying power relations embedded in the narrative and its visual construction. The results show that racism appears throughout the movie in a number of interrelated ways, such as institutional racism, racialized gender discrimination, microaggressions, and cultural racism. These forms are created using subtle cinematic elements, including body language, spatial arrangements, and symbolic references, in addition to overt events and conversation. These symbols serve to legitimize the marginalization of African-American women in the military institution and to normalize white supremacy at the mythological level. This study concludes by showing how racism in movies functions as an ideological framework ingrained in audiovisual representation. By connecting visual signification with structural critique, the merger of CRT and Barthesian semiotics allows for a more thorough analysis, making theoretical, methodological, and empirical contributions to the study of racism in film.